2002
DOI: 10.1242/dev.00166
|View full text |Cite
|
Sign up to set email alerts
|

The early topography of thalamocortical projections is shifted inEbf1andDlx1/2mutant mice

Abstract: The prevailing model to explain the formation of topographic projections in the nervous system stipulates that this process is governed by information located within the projecting and targeted structures. In mammals, different thalamic nuclei establish highly ordered projections with specific neocortical domains and the mechanisms controlling the initial topography of these projections remain to be characterized. To address this issue, we examined Ebf1 -/-embryos in which a subset of thalamic axons does not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 83 publications
(162 reference statements)
7
89
0
Order By: Relevance
“…The functional specialization of each area depends on this input, as does the development of areaspecific functional architecture (Rakic, 1988;Sur et al, 1988;Sur et al, 1990;Rakic et al, 1991;Iwasato et al, 2000;Sharma et al, 2000;Guillery and Sherman, 2002;Kahn and Krubitzer, 2002;Sherman and Guillery, 2002). How thalamocortical innervation is set up in development remains a focus of concentrated investigation (Garel et al, 2002;Hevner et al, 2002;Lopez-Bendito et al, 2002;Dufour et al, 2003;Seibt et al, 2003;Garel and Rubenstein, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The functional specialization of each area depends on this input, as does the development of areaspecific functional architecture (Rakic, 1988;Sur et al, 1988;Sur et al, 1990;Rakic et al, 1991;Iwasato et al, 2000;Sharma et al, 2000;Guillery and Sherman, 2002;Kahn and Krubitzer, 2002;Sherman and Guillery, 2002). How thalamocortical innervation is set up in development remains a focus of concentrated investigation (Garel et al, 2002;Hevner et al, 2002;Lopez-Bendito et al, 2002;Dufour et al, 2003;Seibt et al, 2003;Garel and Rubenstein, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several blue-excited lipophilic dyes exist (DiA, DiO; [12,13,27]; www.probes.com) that allow double labeling, albeit with variable degrees of difficulty and/or success. Some researchers reported that these dyes allowed them to image partial segregation of two labeled neuronal profiles [18], while others reported several problems that were incompletely resolved or not resolvable using DiI in combination with DiA or DiO.…”
Section: Introductionmentioning
confidence: 99%
“…This process of selective fasciculation and contact guidance has been proposed to be required for the highly organized entry of thalamocortical fibers into the cortical plate as well as for corticothalamic fibers to be guided toward their targets (Molnár, 2000;Molnár et al, 2003). Other experimental data, however, suggest that the reciprocal connections between thalamus and cortex can develop independently of each other (Garel et al, 2002;Torii and Levitt, 2005). In II Ϫ/Ϫ IV Ϫ/Ϫ mice, the misguidance of thalamocortical fibers prevents the encounter of thalamocortical and corticofugal fibers and no entry of NFpositive corticothalamic projections into the internal capsule was observed at E14.5 and P1.…”
Section: Discussionmentioning
confidence: 99%